Hp-Positive Chinese Patients Should Undergo Colonoscopy Earlier and More Frequently: The Result of a Cross-Sectional Study Based on 13,037 Cases of Gastrointestinal Endoscopy - Wang, Cheng; Yan, Junbin; He, Beihui; Zhang, Shuo; Xu, Sumei (Frontiers in Oncology, 2021)
Background: In China, the prevalence and mortality of colorectal cancer (CRC) have always been high, and more than 95% of CRC have evolved from colorectal polyps (CPs), especially adenoma. Early detection and treatment of CPs through colonoscopy is essential to reduce the incidence of CRC. Helicobacter pylori (Hp) is regarded as a risk factor for gastritis and gastric cancer and may also be a risk factor for CPs and CRC. However, few studies based on volume clinical cases existed in China to clarify whether Hp is a risk factor of CPs and CRC, whether Hp-positive patients need to advance the time of colonoscopy. The article attempts to make up for the deficiency. Method: The cross-sectional study was conducted based on 13,037 cases without the treatment history of Hp and who accepted the first gastroscopy and colonoscopy simultaneously in The First Affiliated Hospital of Zhejiang Chinese Medical University from January 2018 to December 2019. Pearson x2 test and logistic regression were used to determine whether Hp is a risk factor of CPs and CRC. Multi-factor analysis of variance was used to define the impact of Hp on the CPs prevalence with different ages, gender. Results: For Chinese, Hp is the risk factor of CPs and CRC. The odds ratio (OR) value is 1.228(95% CI, 1.130 to 1.336) and 1.862(95% CI 1.240-2.796), respectively. Hp-positive patients have a higher probability of multiple or large intestinal polyps. However, Hp infection does not increase the incidence of adenomas, nor does it affect the pathological type of adenomas. The OR of HP on the risk of CPs was 1.432(95%CI 1.275-1.608) for the males but increased to 1.937(95%CI 1.334-2.815) for aged 35 to 40. For females, the results were similar. Conclusions: For the Chinese, Hp is a risk factor for CPs and CRC(OR>1); The infection of Hp increased CPs risk in the Chinese of all ages, especially aged 35-40, suggesting Hp-positive patients should accept colonoscopy frequently.